Ethical Problems in Family Firms - Elena Kowalik (Junior Management Science (JUMS), 2023)
Various articles suggest that particular ethical problems occur in family firms, but until now, no attempt has been made to collect and structure available information on them. Based on the systematic review of 110 articles from peer-reviewed academic journals, we show that family firms face a set of unique ethical dilemmas and define those. They can either be family-based or business-based and we uncover the antecedents and outcomes of the processes that family firms employ to solve them. When family firms manage to deal with ethical problems appropriately, they will be rewarded for that in various ways, including improved financial performance and the preservation of potentially all SEW dimensions.
Keywords: 650; Family firms; Business ethics; Socioemotional wealth